ANALISIS KEMAMPUAN DAN KESULITAN SISWA SMP DALAM MENYELESAIKAN SOAL BILANGAN MODEL TIMSS - Prasetyo, Dominikus Arif Budi; Rudhito, Marcellinus Andy (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2016)
Numbers is an important concept in mathematics and one of the tested materials in TIMSSâs study. One of the efforts to increase studentsâ ability in solving TIMSS numbers questions is by developing TIMSS model-numbers questions. This current research investigated studentsâ ability and difficulties in solving TIMSS model-numbers questions, with 31 students in one of junior high schools in Central Java as a sample. Studentsâ ability in solving TIMSS model-numbers questions was measured by test with 32 multiple choice questions, whereas studentsâ difficulties when solving those questions were explored by studentsâ comment sheet. Mean test score indicates that students ability for all content and cognitive domains was moderate. Difficulties experienced by students in solving TIMSS model-numbers questions were misunderstood the meaning of the questions or error in changing fractional forms and making calculations. The results indicated that in addition to having no deep understanding of numbers, studentsâ opportunity to train their ability in solving TIMSS model-numbers questions was still insufficient.